The utility of the apolipoprotein A1 remnant ratio in predicting incidence coronary heart disease in a primary prevention cohort: The Jackson Heart Study. (May 2016) - May, Heidi T; Nelson, John R; Lirette, Seth T; Kulkarni, Krishnaji R; Anderson, Jeffrey L; Griswold, Michael E; Horne, Benjamin D; Correa, Adolfo; Muhlestein, Joseph B
Background: Dyslipidemia plays a significant role in the progression of cardiovascular disease. The apolipoprotein (apo) A1 remnant ratio (apo A1/VLDL3 -C + IDL-C) has recently been shown to be a strong predictor of death/myocardial infarction risk among women >50 years undergoing angiography. However, whether this ratio is associated with coronary heart disease risk among other populations is unknown. We evaluated the apo A1 remnant ratio and its components for coronary heart disease incidence. Design: Observational. Methods: Participants ( N = 4722) of the Jackson Heart Study were evaluated. Baseline clinical characteristics and lipoprotein subfractions (Vertical Auto Profile method) were collected. Cox hazard regression analysis, adjusted by standard cardiovascular risk factors, was utilized to determine associations of lipoproteins with coronary heart disease. Results: Those with new-onset coronary heart disease were older, diabetic, smokers, had less education, used more lipid-lowering medication, and had a more atherogenic lipoprotein profile. After adjustment, the apo A1 remnant ratio (hazard ratio = 0.67 per 1-SD, p = 0.002) was strongly associated with coronary heart disease incidence. This association appears to be driven by the IDL-C denominator (hazard ratio = 1.23 per 1-SD, p = 0.007). Remnants (hazard ratio = 1.21 per 1-SD, p = 0.017), but not apo A1 (hazard ratio = 0.85 per 1-SD, p = 0.121) or VLDL3 -C (hazard ratio = 1.13 per 1-SD, p = 0.120) were associated with coronary heart disease. Standard lipids were not associated with coronary heart disease incidence. Conclusion: We found the apo A1 remnant ratio to be strongly associated with coronary heart disease. This ratio appears to better stratify risk than standard lipids, apo A1, and remnants among a primary prevention cohort of African Americans. Its utility requires further study as a lipoprotein management target for risk reduction.